PERFORMANCE ANALYSIS AND QOS FRAMEWORK OF FLY WIRELESS NETWORK - Pandian, M. Durai (IRO Journal on Sustainable Wireless Systems, 2019)
The spread out of wireless mesh network has made possible the extended range of communication network that are impractical due to environmental changes in a wired access point, these wireless mesh network does not require much competence to set it up as it can be set very fast at a cheap rate, and the conveyancing of messages in it happens by selecting the shortest path, these wireless mesh built-in with irrepressible and invulnerable identities come with an endurance to temporary congestion and individual node failure. This results in an architecture providing a better coverage, flaw indulgent with higher bandwidth compared to other wireless distributed systems. But faces the limitation on power conservation. The battery activated mesh nodes loses their resources on perception, processing and transmission of the data’s, though these batteries or accumulators comes with energy regaining capability still draw backs show up as their nature of energy regaining are unexposed. So the performance analysis of fly wireless network which proposes a uninterrupted wireless mesh networks aims at providing a best measure of performance that is the best quality of service on the meshwork by providing an improved energy gleaning using potency segregation (IGPS) which empowers each node to have self- contained accumulation of energy achieving heightened adaption with energy consumption kept at a minimum. The gross functioning of the proposed is examined on the bases of delay and packet loss to prove the quality of service acquired.